For the love of hops : the practical guide to aroma, bitterness, and the culture of hops - Hieronymus, Stan (Brewers Publications, a division of the Brewers Association, 2012)
"Discusses the science and culture of hops, exploring such topics as history, hop varieties, brewing and dry-hopping techniques, and provides commercial recipes for brewing beer"--